Surveillance for Borrelia spp. in Upland Game Birds in Pennsylvania, USA - Christopher A. Cleveland; Liandrie Swanepoel; Justin D. Brown; Mary Jo Casalena; Lisa Williams; Michael J. Yabsley (Veterinary Sciences, 2020)
The Borrelia genus contains two major clades, the Lyme borreliosis group, which includes the causative agents of Lyme disease/borreliosis (B. burgdorferi sensu stricto and other related B. burgdorferi sensu lato genospecies), and the relapsing fever borreliosis group (B. hermsii, B. turicatae, and B. parkeri). Other unclassified reptile- and echidna-associated Borrelia spp. (i.e., B. turcica and ‘Candidatus Borrelia tachyglossi’, respectively) do not belong in either of these two groups. In North America, Borrelia spp. from both of the major clades are important pathogens of veterinary and public health concern. Lyme disease is of particular interest because the incidence in the northeastern United States continues to increase in both dogs and humans. Birds have a potentially important role in the ecology of Borrelia species because they are hosts for numerous tick vectors and competent hosts for various Borrelia spp. Our goal was to investigate the prevalence of Borrelia spp. in four free-living species of upland game birds in Pennsylvania, USA including wild turkey (Meleagris gallopavo), ruffed grouse (Bonasa umbellus), ring-necked pheasants (Phasianus colchicus), and American woodcock (Scolopax minor). We tested 205 tissue samples (bone marrow and/or spleen samples) from 169 individuals for Borrelia using a flagellin gene (flab) nested PCR, which amplifies all Borrelia species. We detected Borrelia DNA in 12% (24/205) of samples, the highest prevalence was in wild turkeys (16%; 5/31), followed by ruffed grouse (13%; 16/126) and American woodcock (3%; 1/35). All pheasants (n = 13) were negative. We sequenced amplicons from all positive game birds and all were B. burgdorferi sensu stricto. Our results support previous work indicating that certain species of upland game birds are commonly infected with Borrelia species, but unlike previous studies, we did not find any relapsing fever borreliae.